Transformation through Inclusive Innovation: Literature Review and Commentary - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2022)
With this Technical Note, the Independent Science for Development Council (ISDC) seeks to stimulate novel, thoughtful action by CGIAR leaders and researchers that embeds inclusive practices and behaviors in agri-food systems research. Based on a literature review and expert consultations, ISDC finds that concepts and practices of inclusive innovation are emergent and recommends that CGIAR pursue an inclusivity transition in a learning-while-doing mode. Readers are encouraged to: (1) Consider the Reflection Towards Action at the end of Sections 5-8 and find opportunities to discuss within your team, group, or committee. (2) Use the lens of inclusion to vet new and existing mechanisms supplying evidence to decision processes, such as proposal review, monitoring plans, process and performance evaluation, and others. (3) Draw on the ideas presented in this Note for formulation, reconfiguration, or implementation of frameworks that put CGIAR's 2030 strategy into effect (e.g., partner engagement; portfolio performance management; capacity strengthening).